Quality Improvement Project by Reducing None Compliance Rate to The Writing and Approving the Discharge Summery At KFMMC-Dhahran - Rehab Y. AL-Ansari; Mohammed Shehri; Fritzi Esguerra; Sultan Otaibi; Muhanad Alghamdi; Abdulelah Alharbi; Abdulaziz AlShamrani; Nawaf Zakary; Nada Rajab Alzahrani (Asia Pacific Journal of Health Management)
Background& aim: More than 300,000 active patients' medical records are kept at our institute. In 2021 only 19% of respondents (consultant in charge of the patient) agreed to the discharge summary (DC). Consequently, a corrective action plan was put into place to increase the compliance rate to policy to at least 90%.